Factors Influencing Private Practitioners to Report Tuberculosis Cases - Anneke Rosma; Chiho Yamazaki; Satomi Kameo; Dewi M. Herawati; Rovina Ruslami; Ardini Raksanagara; Hiroshi Koyama (Universitas Padjadjaran, Indonesia)
One of the key elements in tuberculosis (TB) management is a system for recording and reporting, in which every health care provider needs to report every TB case to an authorized primary health center (PHC) to support effective treatment. This study was conducted to investigate the present condition of TB recording and reporting system and evaluate several factors that might influence PP behavior regarding the reporting of TB cases to a PHC in Bandung, Indonesia. Face-to-face interviews with PP and the head of the PHC were performed. Data were coded, categorized, and analyzed statistically by Fischer’s exact test. We found that there were four factors influencing the reporting of TB cases by PP to PHC, including self-awareness, ignorance, lack of time, and poor implementation of recording and reporting system. The level of PP self-awareness was significantly associated with the reporting of TB cases (p<0.05). Private sector involvement, improvement in the recording of treatment follow-up, and the use of electronic based reporting were considered important by participants to construct a well-established recording and reporting system for TB cases. In conclusion, there are still room for improvement in the reporting and recording system of TB cases in PHC.Keywords: recording, reporting, tuberculosis, self-awareness, practitioners